Four Acid-Base Disturbances in a Critically-Ill Patient Undergoing Emergent Abdominal Surgery. (4th July 2022) - Mavrothalassitis, Orestes; Thind, Balkarn S.; Agrawal, Ashish
Abstract : Lactic acidosis is common in critically-ill surgical patients, but not all perioperative acid-base imbalances are attributable to tissue hypoperfusion. Other causes of acid-base abnormalities can be missed when focused on acute resuscitation of a surgical pathology. This report presents the case of a 60-year-old woman with no past medical history who underwent exploratory laparotomy for umbilical hernia with incarcerated and perforated bowel whose perioperative management was complicated by four acid-base disturbances, including starvation ketosis. This case highlights the importance of early recognition of acid-base imbalances to explain concurrent medical pathology and accurately predict a patient's expected post-operative course.